Cognitive approach application for the typological classification of regions by level of industrial development - Чуріканова, Олена Юріївна (Technology audit and production reserves, 2015)
The article it is focused on problems of typological classification of regions in terms of industrial development. It is noted that existing approaches to typological classification of regions based only on quantitative indicators of regions. It is proposed to perform the typological classification of regions in terms of industrial development not in quantitative terms, but the degree of connection between them. To solve this problem it is proposed use of the cognitive approach. In the article it is grounded relevance of cognitive approach usage to achieve the study aims. It is selected a group of indicators (concepts) that characterize the industrial development of the region. It is investigated the relationship between selected concepts. It is completed construction of cognitive maps of industrial development of regions. It is emphasized the opportunities to highlight weaknesses in the industrial development of the region based on cognitive maps for the effective functioning of the whole system and making effective management decisions. The algorithm of typological classification of regions in terms of industrial development as a basis for cognitive maps is shown. It is noted future prospects of research in the area of the cognitive approach application to typological classification of regions.